Mitigating risks of students use of study drugs through understanding motivations for use and applying harm reduction theory: a literature review - Dor David Abelman (BMC, 2017)
Abstract As postsecondary students' use of "study drugs" becomes more popular with increasingly reported negative effects on health and academic performance, failing prohibitionist policies to reduce consumption, and ambiguity in literature towards best practices to address this population, we present a literature review that seeks effective solutions educational institutions can apply to improve outcomes for students who use drugs. Motivations for use, effects of the substances, an analysis of efforts to control use from educational institutions, and suggestions on promoting most effective outcomes based on harm reduction, are described. Theory, quantitative, and qualitative works from systematic reviews, cohort studies, and epidemiological assessments are examined on the "study drugs" methylphenidate, dextroamphetamine, and amphetamine, also known as Adderall, Ritalin, Focalin, and Concerta. There is a focus on postsecondary students ages 18-25 in North America. Results show important risk factors for drug use including low perceived self-efficacy or enjoyment in courses, poor accommodation of special needs, reliance on external validation, having a low GPA, and experiencing a mental health issue. There is much misconception on the health and academic effects of these drugs in literature, among students, and on online knowledge sources. We suggest these drugs do not improve GPA and learning, while they might temporarily increase memory, but with detrimental negative health effects. Campaigns that address underlying factors of use can be most successful in mitigating harms.